Investigation of non-isothermal pyrolysis kinetics of waste industrial hemp stem by three-parallel-reaction model. (March 2022) - Chen, Fangjun; Zhang, Fengxia; Yang, Shiliang; Liu, Huili; Wang, Hua; Hu, Jianhang
Graphical abstract: Highlights: Waste IHS was used as feedstock to produce biochar. First detailed investigation on non-isothermal pyrolysis kinetics of IHS. The reaction mechanism model of IHS pyrolysis was reconstructed. The TPR model well described the pyrolysis process of IHS. Abstract: The evaluation of pyrolysis kinetics for waste industrial hemp stem (IHS) is essential to achieve the high-value utilization of agricultural waste. In present study, firstly, non-isothermal pyrolysis experiments of IHS were performed at different heating rates using a thermogravimetric analyzer. Then, the kinetic triplets (apparent activation energy, pre-exponential factor, and reaction mechanism) of the three pseudo components for IHS (hemicellulose, cellulose, and lignin) were determined by a three-parallel-reaction model. Moreover, the pyrolysis products were also characterized via FTIR and SEM. The results showed that the apparent activation energies of hemicellulose, cellulose and lignin were 86.523, 113.257 and 197.961 kJ/mol, respectively; the pre-exponential factors were 6.887 × 10 7, 8.179 × 10 9 and 1.801 × 10 15 s −1, respectively; and the reaction mechanism functions were f (α) = α 1.35629 (1-α) 0.34832 [-ln(1-α)] −1.20128, f (α) = α 3.42900 (1-α) 0.01288 [-ln(1-α)] -2.84445, f (α) = α 0.68738 (1-α) 3.09313 [-ln(1-α)] -1.58522, respectively. The release temperature for volatile products of IHS pyrolysis was mainly between 440 and 840 K. IHS as an agricultural waste is a suitable feedstock to produce renewable energy.